2005
DOI: 10.1359/jbmr.050518
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Paget's Disease of Bone in Italy

Abstract: We examined the prevalence of PDB in Italy from radiological, scintigraphic, and biochemical surveys in two Italian towns. Prevalence rates varied from 0.7% to 2.4%, were higher in males than in females, and slightly differed between the two towns. Unlike previous studies in populations of British descent, no secular trend for a decreasing prevalence emerged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 16 publications
2
32
1
2
Order By: Relevance
“…The incidence in the UK is currently similar to that of Caucasian populations in other countries. In Italy, a recent prevalence study (12) has been conducted in the cities of Turin and Siena on the basis of x-ray, scintigraphy and biochemical tests. Among over 60 years of age, the overall incidence of the disease accounts for just over 1% and is greater among males with no significant differences between the two cities.…”
mentioning
confidence: 99%
“…The incidence in the UK is currently similar to that of Caucasian populations in other countries. In Italy, a recent prevalence study (12) has been conducted in the cities of Turin and Siena on the basis of x-ray, scintigraphy and biochemical tests. Among over 60 years of age, the overall incidence of the disease accounts for just over 1% and is greater among males with no significant differences between the two cities.…”
mentioning
confidence: 99%
“…Moreover, an Italian survey on radiological, scintigraphic and biochemical data, showed that the prevalence of PDB in Italy, unlike the studies on British descent populations, did not exhibit a decreased secular trend [10]; (ii) a significant decline of the PDB-related mortality has been more recently reported in a US study (population of Olmsted County, MN) in which it has been showed that overall survival in the PDB analysed population was slightly better than expected when compared with white Minnesota residents, especially in affected male. Moreover, an increased risk of mortality resulting from cancer, cardiovascular disease, pulmonary disease or gastrointestinal disease has not been reported in this study [11]; (iii) a drastic fall down of PDB prevalence (standardized both for age and gender) between 1974 and 1994 (follow-up prevalence study in 10 towns in Great Britain), as also observed in other European Countries; on the contrary, a previous US survey on the incidence of PDB (still from Olmsted County, MN), covering the period 1950 through 1994, revealed an increased incidence over the first part of the study period and then a decline [12].…”
Section: Secular Trends Of Paget's Disease Of Bone: Conflicting Resultsmentioning
confidence: 86%
“…Finally, some studies have failed to show a reduction in disease prevalence or severity, but these have been undertaken either in low prevalence areas or over a relatively short time and therefore were underpowered to detect such change. (22,23) There has been much speculation as to what environmental agents might be important. Suggestions have ranged from childhood diet, physical activity, oral bacteria, viruses, zoonotic infections, to occupational exposures.…”
Section: Is the Prevalence Of Paget's Disease Of Bone Decreasing? P11mentioning
confidence: 99%